Three-Dimensional Culture Promotes the Differentiation of Human Dental Pulp Mesenchymal Stem Cells Into Insulin-Producing Cells for Improving the Diabetes Therapy - Xu, Bingbing; Fan, Daoyang; Zhao, Yunshan; Li, Jing; Wang, Zhendong; Wang, Jianhua; Wang, Xiuwei; Guan, Zhen; Niu, Bo (Frontiers in Pharmacology, 2020)
Introduction Diabetes is a metabolic disease with a high incidence and serious harm to human health. Islet β-cell function defects can occur in the late stage of type 1 diabetes and type 2 diabetes. Studies have shown that stem cell is a promising new approach in bioengineering regenerative medicine. In the study of stem cell differentiation, three-dimensional (3D) cell culture is more capable of mimicking the microenvironment of cell growth in vivo than two-dimensional (2D) cell culture. The natural contact between cells and cells, and cells and extracellular matrix can regulate the development process and promote the formation of the artificial regenerative organs and organization. Type IV, VI collagen and laminin are the most abundant extracellular matrix components in islets. Matrigel, a basement membrane matrix biomaterial rich in laminin and collagen IV. Materials and Methods We used Matrigel biomaterial to physically embed human dental pulp stem cells (hDPSCs) to provide vector and 3D culture conditions for cells, and we explored and compared the preparation methods and preliminary mechanisms of differentiation of hDPSCs into insulin-producing cells (IPCs) under 2D or 3D culture conditions.We first designed and screened the strategy by mimicking the critical events of pancreatogenesis in vivo, and succeeded in establishing a new method for obtaining IPCs from hDPSCs. Activin A, Noggin, and small molecule compounds were used to synergistically induce hDPSCs to differentiate into definitive endoderm-like cells, pancreatic progenitor like cells and IPCs step by step under 2D culture conditions. Then, we used Matrigel to simulate the microenvironment in vivo, induced hDPSCs to differentiate into IPCs in Matrigel, evaluated and compared the efficiency between 2D and 3D culture conditions. Results The results showed that the synergistic combination of growth factors and small molecule compounds and 3D culture promoted the differentiation of hDPSCs into IPCs, significantly enhancing the release of insulin and C-peptide from IPCs. Discussion Significant support is provided for obtaining a large number of functional IPCs for disease modeling and final cell therapy in regenerative medicine.